2014
DOI: 10.1161/strokeaha.114.006488
|View full text |Cite
|
Sign up to set email alerts
|

18fdg-Pet-Ct

Abstract: A lthough the degree of lumen obstruction is a relevant marker of the risk of stroke, the recognition of the role of the vulnerable plaque has opened new insights in the field of atherothrombotic stroke. [1][2][3][4] Vulnerability is dictated in part by plaque morphology, which, in turn, is influenced by pathophysiologic mechanisms at the cellular and molecular level. Thus, a certain number of features of plaque morphology may play an important role in the occurrence of cerebrovascular events. [5][6][7] An uns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…4. PET-CT supports and demonstrates the inflammationischemia relationship by revealing pro-inflammatory macrophages in the atherosclerotic plaque (18fluorodeoxyglucose capture is directly proportional to the number of macrophages present in the atheroma plate) [8][9][10].…”
mentioning
confidence: 76%
“…4. PET-CT supports and demonstrates the inflammationischemia relationship by revealing pro-inflammatory macrophages in the atherosclerotic plaque (18fluorodeoxyglucose capture is directly proportional to the number of macrophages present in the atheroma plate) [8][9][10].…”
mentioning
confidence: 76%
“…Several studies recently assessed the diagnostic potential of using 18 F-fluorodeoxyglucose PET ( 18 F-FDG PET) or 18 F-FDG PET/CT to evaluate plaque inflammation, and promising results have been reported. These studies report that 18 F-FDG PET or 18 F-FDG PET/CT can accurately detect high-risk carotid plaques [ 129 - 131 ] ( Figure 14 ). There are significant correlations between the histologic findings and degree of inflammation on 18 F-FDG [ 132 , 133 ].…”
Section: Vessel Wall Imaging Techniquesmentioning
confidence: 99%
“…However, it has been repeatedly reported that arterial calcification does not always accord with FDG uptake ( 37 38 39 ), probably because FDG uptake reflects the present activity whereas calcifications on CT are the end-products of inflammation. Consequently, FDG uptake is related to cardiovascular events or stroke ( 40 41 ), and probably is a better predictor for vascular events than calcifications on CT ( 42 ). Based on this background, FDG PET has been used for assessing inflammation activity in the case of drug treatment ( 43 44 ).…”
Section: Imaging Methodsmentioning
confidence: 99%
“…However, there is no consensus for the selection of an appropriate quantitative index for atherosclerosis, in contrast to cancers where the maximal SUV is commonly utilized as an index reflecting the most malignant components of a lesion. Among reported FDG PET studies on plaque imaging, some adopted the maximal SUV ( 32 38 39 41 42 ), whereas others adopted the mean SUV as a quantitative index ( 33 36 40 94 ). Based on these values, additional semi-quantitative indices were calculated, such as the target-to-reference tissue ratio (TRR; also called target-to-background ratio, TBR) or the lesion-to-normal ratio (LNR) ( Table 1 ).…”
Section: Considerations Regarding Imaging Technologymentioning
confidence: 99%